2017
DOI: 10.1289/ehp44
|View full text |Cite
|
Sign up to set email alerts
|

Time-series Analysis of Heat Waves and Emergency Department Visits in Atlanta, 1993 to 2012

Abstract: Background:Heat waves are extreme weather events that have been associated with adverse health outcomes. However, there is limited knowledge of heat waves’ impact on population morbidity, such as emergency department (ED) visits.Objectives:We investigated associations between heat waves and ED visits for 17 outcomes in Atlanta over a 20-year period, 1993–2012.Methods:Associations were estimated using Poisson log-linear models controlling for continuous air temperature, dew-point temperature, day of week, holid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…Two studies in Adelaide, Australia, showed increased admissions for renal disease during heatwaves through all ages, by 10% and 13%, respectively [ 10 , 11 ], and another study in Adelaide also identified an association between temperature and renal disease [ 12 ]. International studies have shown similar results [ 3 , 13 15 ]. Studies in the United States of America (USA) linked incremental rises in same-day apparent temperatures to an increased occurrence of renal disease and acute kidney injury (AKI, also known as acute renal failure) [ 1 , 13 ].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Two studies in Adelaide, Australia, showed increased admissions for renal disease during heatwaves through all ages, by 10% and 13%, respectively [ 10 , 11 ], and another study in Adelaide also identified an association between temperature and renal disease [ 12 ]. International studies have shown similar results [ 3 , 13 15 ]. Studies in the United States of America (USA) linked incremental rises in same-day apparent temperatures to an increased occurrence of renal disease and acute kidney injury (AKI, also known as acute renal failure) [ 1 , 13 ].…”
Section: Introductionsupporting
confidence: 64%
“…In many cities, high temperatures have been linked to an increased occurrence of AKI [ 3 , 11 , 13 , 15 17 ] and chronic kidney disease (CKD, also known as chronic renal failure) [ 18 , 19 ]. A study in Sydney, Australia, reported that the incidence of AKI and renal failure (AKI and CKD combined) increased if the daily temperature was above the 95th percentile range for one day, and this further increased if the high temperature persisted for three days [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest opportunities for improvement and for refinement of prevention messaging as well as coordination between meteorological and public health authorities at multiple levels before, during, and after periods of extreme heat. that morbidity impacts, when available, may be most appropriate, as these outcomes are more prevalent than mortality endpoints (14,15).…”
Section: Significancementioning
confidence: 99%
“…Wang et al (2012) indicated a signi cant association between heat waves and diabetes mortality of the elderly aged over 75 years. No signi cant association between heat waves and diabetes was found in other four studies (Campbell et al 2019;Sherbakov et al 2018;Wilson et al 2013;Chen et al 2017).…”
Section: Overall Analysis Of Extreme Temperatures On Diabetesmentioning
confidence: 71%